Poly(ADP-ribose) polymerases as modulators of mitochondrial activity. (February 2015) - Bai, Peter; Nagy, Lilla; Fodor, Tamás; Liaudet, Lucas; Pacher, Pal
Highlights Activation of poly(ADP-ribose) polymerases-1 and -2 (PARP-1 and PARP-2) deteriorates mitochondrial activity. NAD+ and ATP degradation are not coupled to each other upon PARP activation. PARPs interact with transcription factors modulating mitochondrial activity. PARPs can be positive regulators of mitochondrial output under sublethal stress. PARP inhibition is an attractive target for treating mitochondrial dysfunction.